1993
DOI: 10.1073/pnas.90.15.6909
|View full text |Cite
|
Sign up to set email alerts
|

"Diversomers": an approach to nonpeptide, nonoligomeric chemical diversity.

Abstract: Solid-phase chemistry, organic synthesis, and an apparatus for multiple, simultaneous synthesis have been combined to generate libraries of organic compounds ("diversomers"). Arrays of compounds were synthesized over two to three steps incorporating chemically diverse building blocks on a polystyrene-based solid support in a multiple, simultaneous manner. The generality of this approach is illustrated by the syntheses of dipeptides, hydantoins, and benzodiazepines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
110
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(112 citation statements)
references
References 26 publications
0
110
0
2
Order By: Relevance
“…[9][10][11]; (ii) spatially addressable syntheses in which the structure of a compound is deduced from its position on an array (2,(12)(13)(14); and (iii) split synthesis procedures, whereby compounds are built up on solid-phase beads, each of which has a unique history throughout the randomization steps and hence a unique structure-e.g., "one-bead-one-peptide" (4,6). The appropriate synthetic strategies can be modified in a number of ways so that with each component introduced by a combinatorial step, a conjugate "tag" is added in a parallel step; these coding sequences or tags are read subsequently to decode the steps used for the construction of the structure on any given bead.…”
mentioning
confidence: 99%
“…[9][10][11]; (ii) spatially addressable syntheses in which the structure of a compound is deduced from its position on an array (2,(12)(13)(14); and (iii) split synthesis procedures, whereby compounds are built up on solid-phase beads, each of which has a unique history throughout the randomization steps and hence a unique structure-e.g., "one-bead-one-peptide" (4,6). The appropriate synthetic strategies can be modified in a number of ways so that with each component introduced by a combinatorial step, a conjugate "tag" is added in a parallel step; these coding sequences or tags are read subsequently to decode the steps used for the construction of the structure on any given bead.…”
mentioning
confidence: 99%
“…3,4 Pilot experiments were initiated utilizing commercially available FMOC-glycine as a source of DBF. However, it was found that addition of 20% piperidine/DMF to this compound formed a precipitate (presumably piperidinium glycinate), which could potentially complicate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A common strategy in solid-phase synthesis is cyclization-assisted cleavage which combines the linker cleavage and ring formation in a single reaction step [57]. One of the first examples of cyclative cleavage of polymer support in solid-phase synthesis was developed in the preparation of hydantoins [58].…”
Section: Introductionmentioning
confidence: 99%